Different patterns of postprandial lipoprotein metabolism in normal, type IIa, type III, and type IV hyperlipoproteinemic individuals. Effects of treatment with cholestyramine and gemfibrozil. - Weintraub, M S (1987)
To study exogenous fat metabolism, we used the vitamin A-fat loading test, which specifically labels intestinally derived lipoproteins with retinyl palmitate (RP). Postprandial RP concentrations were followed in total plasma, and chylomicron (Sf greater than 1,000) and nonchylomicron (Sf less than 1,000) fractions. In normal subjects postprandial lipoproteins were present for more than 14 h, and chylomicron levels correlated inversely with lipoprotein lipase activity and fasting high density lipoprotein (HDL) cholesterol levels and nonchylomicron levels correlated inversely with hepatic triglyceride lipase activity. The main abnormality in type IV patients was a 5.6-fold increase in the chylomicron fraction, whereas in type III patients it was a 6.4-fold increase in nonchylomicrons. Type IIa patients had abnormally low chylomicron fractions. In type IV patients gemfibrozil decreased, whereas in type IIa patients cholestyramine increased the chylomicron fraction 66 and 88%, respectively. This study demonstrates an unexpectedly large magnitude and long duration of postprandial lipemia in normal subjects and patients. These particles are potentially atherogenic, and their role in human atherosclerosis warrants further study.